2023
DOI: 10.1371/journal.pone.0279965
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in body height according to educational level. A descriptive study from the Tromsø Study 1979–2016

Abstract: Objectives The objective of our study was to describe time trends in body height according to attained educational level in women and men in Norway. Methods We used previously collected data from six repeated cross-sectional studies in the population based Tromsø Study 1979–2016. Measured body height in cm and self-reported educational level were the primary outcome measures. We included 31 466 women and men aged 30–49 years, born between 1930 and 1977. Participants were stratified by 10-year birth cohorts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As a result, average somatic parameter values increased across generations (Baten & Blum, 2012;Bogin, 2021;Hatton, 2014;Hatton & Bray, 2010;Steckel, 2012). Similarly, recent studies have shown a comparable secular trend and intergenerational dynamics of height associated with changes in the socioeconomic and political context in Austria (Kirchengast et al, 2022), Norway (Arntsen et al, 2023), andSpain (S anchez-García et al, 2023).…”
Section: T a B L E 3 Correlations Between Anthropometric And Socioeco...mentioning
confidence: 69%
“…As a result, average somatic parameter values increased across generations (Baten & Blum, 2012;Bogin, 2021;Hatton, 2014;Hatton & Bray, 2010;Steckel, 2012). Similarly, recent studies have shown a comparable secular trend and intergenerational dynamics of height associated with changes in the socioeconomic and political context in Austria (Kirchengast et al, 2022), Norway (Arntsen et al, 2023), andSpain (S anchez-García et al, 2023).…”
Section: T a B L E 3 Correlations Between Anthropometric And Socioeco...mentioning
confidence: 69%
“…The models were built only with age and the 88 CSLV parameters. We included age because there are well known age cohort effects on height[35,36]. Older people grew up with different diet and nutrition than younger people and are shorter on average.…”
Section: Methodsmentioning
confidence: 99%